Teaching case. Gamification in higher education: turning training in face-to-face and online studies - del Castillo, Ángel (Journal of Management and Business Education, 2022)
The profile of university students has changed in recent years. The use of the Internet and social networks has fostered immediacy in everyday life. Added to this is the fact that in recent years the number of students known as “sisi” generation has increased, that is, students who study and work at the same time. For this student profile, not only is a master class enough, but, given the effort they make to be able to train -in person or online (e-learning)- we must, at least, take into account different techniques or tools that can help encourage participation, motivate students and facilitate the acquisition and assimilation of the knowledge exposed in the training sessions. In this line, we present a teaching case in which gamification tools applicable to education were used in order to report an experience that makes the use of this type of programs or gamification techniques to be valued and taken as a reference when teaching. in a context of higher education both in the face-to-face environment and in the online environment. In the present study, the experience of applying gamification tools or techniques, both in face-to-face studies and in online studies, has been satisfactory for the students and, as they indicate, has helped them in their learning. In line with other authors, our didactic case corroborates the results of the improvement in the understanding and learning of students in higher education.